1987
DOI: 10.1111/j.1600-0404.1987.tb07906.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of IgG and albumin in CSF and serum from multiple sclerosis patients by enzyme-linked immunosorbent assay

Abstract: Immunoglobulin G (IgG) and albumin from unconcentrated cerebrospinal fluid (CSF) and serum of patients with multiple sclerosis (MS) and non-MS controls were quantitated using enzyme-linked immunosorbent assay (ELISA). The IgG levels, IgG/albumin ratios and IgG indexes were significantly increased in CSF of MS patients compared to those of non-MS controls. The method is sensitive, rapid and reproducible and can be applied to routine laboratory use for quantitation of IgG and albumin in unconcentrated CSF from h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In addition, serum UA, Tbil, Ibil and albumin levels of patients with NMO were almost lower than those of patients with MS although there were no significant differences between them. However, low serum UA and albumin levels in patients with MS have been reported by us and other groups [2][3][4][5]15]. Even more, a study performed by Liu Y, et al [16] indicated that serum bilirubin concentration was decreased in mice of experimental autoimmune encephalomyelitis (EAE) [16], an animal model of MS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, serum UA, Tbil, Ibil and albumin levels of patients with NMO were almost lower than those of patients with MS although there were no significant differences between them. However, low serum UA and albumin levels in patients with MS have been reported by us and other groups [2][3][4][5]15]. Even more, a study performed by Liu Y, et al [16] indicated that serum bilirubin concentration was decreased in mice of experimental autoimmune encephalomyelitis (EAE) [16], an animal model of MS.…”
Section: Discussionmentioning
confidence: 99%
“…The implication of immunoglobulins in MScl pathogenesis has been reported repeatedly. Elevated immunoglobulin G (IgG) levels as a marker for disease activity, , extra oligoclonal IgG bands as a potential marker for progression from CIS to MScl, and free immunoglobulin κ light chains in MScl cerebrospinal fluid have all been extensively researched. Considering the fact that immunoglobulin levels in the MScl samples used in this study were significantly higher than in non-inflammatory controls, it was expected that some immunoglobulin peptides would be identified as differentially abundant using this MALDI−FT-ICR analysis method.…”
Section: Discussionmentioning
confidence: 99%